Nutrition and cancer prevention: how well are we doing? - Mohamed, Hamid Jan Jan (World Nutrition Journal, 2025)
Southeast Asia faces a dual burden of malnutrition and rising noncommunicable diseases, including cancer, many of which are influenced by diet and lifestyle. This review examines how well countries in Southeast Asia are aligning with nutritional practices known to reduce cancer risk